Social Perception of Adolescents with Ambivert Personality When Doing Activities Alone in Public Spaces - Bayu Anggoro; Vera Imanti (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
Public spaces are currently widely used by the community, especially after the end of the COVID-19 pandemic. Adolescents are actively utilizing facilities in public spaces. Adolescents are in a phase where they have a lot to say in social interactions. This phase is a chance for them to find their identity and will also affect their personalities. Carl Jung identified three types of personalities: extroverts, introverts, and ambiverts. Ambivert is a personality type that has good adaptability. The social environment or culture can influence personality. The social culture that has developed in Indonesia is collectivist. Collectivism requires the community to be bound by each other. The manifestations of collectivism are neighborhood associations, community associations, and community service. Social perception is a person's ability to understand other people with their sense of sight. The phenomenon that can be found in this research is the activity of adolescents with ambivert personalities alone in public spaces. The method used in this research is qualitative with a phenomenological approach. The data collection used unstructured and semi-structured interview techniques. This activity certainly arises from social perceptions of the surrounding environment. Perceptions arise because the habit is still rare in our society. Perceptions that arise include that a person has no friends, has an introverted personality, wants to spend time alone, isn't good at socializing, or some consider it a normal thing to do. As a result of these perceptions, adolescents with ambivert personalities feel uncomfortable doing activities alone in public spaces.